Older assistant nurses' motivation for a full or extended working life. Issue 12 (16th July 2018) - Gyllensten, Kristina; Wentz, Kerstin; Håkansson, Carita; Hagberg, Mats; Nilsson, Kerstin
Abstract: The aim of this study was to explore older workers' motivation for a full or extended working life. With particular focus on assistant nurses aged 55–64 years, working in the elderly care sector. Focus group interviews were conducted with five different groups of assistant nurses. Inductive thematic analysis was used to analyse the interviews and five main themes were developed from the data: 'Organisational issues', 'Health-related problems', 'Private issues', 'Meaningfulness and appreciation' and 'Social support'. Several of the main themes concerned problems with too high work demands of the assistant nurses. These findings suggest that it is important to improve the working conditions of assistant nurses in order to create a more sustainable working life. Increasing the number of staff and improving recovery opportunities and work–life balance could be important steps to improving the working conditions for this group. Finally, upgrading the competency and professionalism of assistant nurses could help to increase the motivation for a full or extended working life.